Strong toxic gas detection on penta-BCP monolayers: Insights from DFT calculations - Thanasee Thanasarnsurapong; Suchanuch Sringamprom; Pakpoom Reunchan; Weekit Sirisaksoontorn; Sirichok Jungthawan; Piyanooch Nedkun; Jariyanee Prasongkit; Adisak Boonchun (Talanta Open)
Rapid and accurate detection of toxic gases remains important for industrial safety and environmental well-being. This study examines the potential of penta-BCP monolayer as a high-performance toxic gas sensor utilizing the robust framework of density functional theory (DFT). Penta-BCP exhibits strong and selective interactions with specific toxic gas molecules, including CO, NO, and NO2. This results in the remarkable ability to readily capture these harmful gases while demonstrating minimal interaction with non-toxic counterparts such as H2, N2, CO2, and CH4, underlining its exceptional selectivity. Furthermore, penta-BCP has a significantly shorter recovery time for NO and NO2 gases compared to penta-BCN, which has a similar structure. These findings collectively position penta-BCP as a frontrunner for the next generation of toxic gas sensors, paving the way for enhanced environmental monitoring and improved public health protection.